Optimizing healthcare for blood donors at risk of transfusion-transmissible infections: pre-implementation mixed methods protocol - Juan Macalupu; Elsa González-Lagos; Sarah Gimbel; Eduardo Gotuzzo (Global Health Action)
In the Peruvian Amazon, a significant proportion of replacement blood donors test reactive for HIV, HTLV-1/2, and other transfusion-transmissible infections but often receive no subsequent care. Optimizing healthcare for these individuals can mitigate adverse outcomes by enabling early diagnosis and management. Effective coordination between Blood Bank and Infectious Diseases services is essential to provide comprehensive care. To address this challenge, this study applies an Implementation Science approach to design and assess an innovation that enhances healthcare for blood donors affected by transfusion-transmissible infections. A pre-implementation mixed methods study will be conducted at two hospitals in the Peruvian Amazon, employing the Consolidated Framework for Implementation Research (CFIR) and a systems engineering tool (mapping). The study will focus on the inner setting domain of CFIR and map the care continuum to identify contextual determinants that may influence implementation. It has three specific aims planned for the future: first, to use a convergent mixed methods approach to examine the care continuum of blood donors and the inner settings; second, to co-design an innovation through qualitative and participatory methods, integrating Blood Bank and Infectious Diseases services via the hospital information management system; and third, to evaluate the feasibility, appropriateness, and acceptability of the co-designed innovation through a pilot. Replacement blood donation and fragmented healthcare systems are common challenges in other low- and middle-income countries. The findings of this study can inform future implementation research and policy in similar settings.